The Effect of Using Autonomous Learning Model by Duolingo-Assisted to Improve Students’ Vocabulary Mastery at VIII Class of SMPN 3 Buton Tengah - Rais Abin; Netty Huzniati Andas (PT ARRUS Intelektual Indonesia, 2022)
The aim of this study was to find out whether the use of the Autonomous Learning Model by Duolingo-assisted has an effect on increasing the vocabulary mastery of the eighth grade students of SMPN 3 Buteng. Purposive sampling was used to select 29 students in VIII grade class as sample of this research. This study applied a pre-experimental method using one class pretest and posttest. To collect data and information, researchers used tests, distributed questionnaires, and conducted interviews. From the analysis result, the researcher found that the students' average score increased from 60.94 to 86.83. Hypothesis analysis at a significant level of 0.05 showed that the value of Tcount was higher than the value of Ttable (14,662>2,048) so that H0 was rejected and H1 was accepted. This means that the treatment given to students, namely the Autonomous Learning Model assisted by the Duolingo application has an effect to increase vocabulary. Autonomous Learning assisted by the Duolingo application is very appropriate to use in teaching vocabulary because with this learning model students were encouraged to be more independent and responsible in learning English without others help. Duolingo as a learning media made students more interested in learning English because this application is equipped with complete features that make it easier for students to learn vocabulary.